The effect of employee performance on emotional intelligence, intellectual intelligence, and spiritual intelligence - Purwanggono, Cuk Jaka (Enrichment : Journal of Management, 2023)
This research analyzes and examines intellectual intelligence, emotional intelligence, and spiritual intelligence on the performance of cardiac specialist employees at SMC Telogorejo Hospital. This is qualitative research using primary data from 51 cardiac specialist employees at SMC Telogorejo Hospital as respondents. Data collection was carried out using a survey through questionnaires distributed to respondents. In this research, the data testing includes reliability tests, classical assumption tests, validity tests, and t-tests to prove research hypotheses which are measured using the Statistical Package for The Social Sciences (SPSS) 16.0 software. In this study, the results showed that in the T-Test, intellectual intelligence does not have a negative (-0.92) and significant (0.927) effect on employee performance, as well as emotional intelligence does not have a negative (-0.691) and significant effect (0.493) on an employee's performance. Furthermore, spiritual intelligence has a positive (2.941) and significant (0.005) effect on the performance of an employee at Telogorejo Hospital.